If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19z + -3(z + -6) = 66 Reorder the terms: 19z + -3(-6 + z) = 66 19z + (-6 * -3 + z * -3) = 66 19z + (18 + -3z) = 66 Reorder the terms: 18 + 19z + -3z = 66 Combine like terms: 19z + -3z = 16z 18 + 16z = 66 Solving 18 + 16z = 66 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 16z = 66 + -18 Combine like terms: 18 + -18 = 0 0 + 16z = 66 + -18 16z = 66 + -18 Combine like terms: 66 + -18 = 48 16z = 48 Divide each side by '16'. z = 3 Simplifying z = 3
| 7x^2=3x+5 | | 9b^2-24bt+16t^2= | | 24f=156 | | 16.8=17.6t-0.8t^2 | | K+17=2 | | 5y+4(y-7)=4(y+2)-2 | | 169b^2-225= | | K+5=7 | | m+1-2=5-6 | | 12s^2-29sb+14b^2= | | 9+5s-6=9s+3-3s | | 19-4x=-6x+13 | | x^2-11x-8712=0 | | 3(5s+4)-5s=2(5s+2)-9 | | 3a-21a+6a-42= | | 6x+6=6(x+7) | | .1(x+40)+1.5x=68 | | 12(3x+3)-6(2x-6)=4x-68 | | (9x^2)(x)=9x^3 | | 8(n+7)=2(28+4n) | | 14x^4-10x^2=0 | | 10x^4-10x^2=0 | | x+14=x+10 | | -x^2-3x=2x+6 | | x^2+3x=2x+6 | | 6+7x=4+3x | | 8x+5=40-3 | | z-9=2z+1+4z | | 4(k-1)=2(k+1) | | 75x-1=30x+89 | | (0.36(6)+0.04x)=(0.12(24+x)) | | 4m^3-16m^2+36m=0 |